Penentuan Daya Tampung Beban Pencemaran Sungai Rawas Pada Segmen PT. Kirana Windu Di Kecamatan Rawas Ulu Kabupaten Musi Rawas Utara - Sianipar, Renov; Brata, Bieng; Yurike, Yurike (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
ABSTRACT The rapid development of development, including industrialization activities around the Rawas river, which was designated as class I water in 2005, has certainly contributed to reducing the capacity of the Rawas river itself. This research aims to look at the current conditions regarding the capacity to carry the pollutant load of the Rawas River in the PT Kirana Windu segment and at the same time also provide input and considerations regarding determining waste water quality standards for businesses and/or activities that will operate in the future. To calculate the pollutant load capacity of the Rawas River using the Mass Balance method, samples of Rawas River water (point 1), domestic wastewater (point 2) and production wastewater (point 3) were taken for further analysis at the UPTD Environmental Laboratory of the Regency Environmental Service. Musi Rawas which has been accredited. The calculation results show that the Rawas river (downstream) has a capacity for the BOD parameter of 1.7 mg/L, a TSS parameter of 35 mg/l, and a capacity for the COD parameter that is close to critical at only <1 mg/L. Meanwhile the capacity for the fat oil parameter is at the maximum limit of 1 mg/L, the capacity for the ammonia parameter is 0.068 mg/L and the capacity is very high for the Total Coliform parameter and the N-Total parameter. Keywords: Capacity, Rawas River, Water Class